Managerial Particulars of Marketing Research for Companies Producing White Sea Buckthorn - Mirza, Sergiu; Balan, Igor; Lupu, Constantin (The Journal of Accounting and Management, 2024)
One of the most important characteristics of any agricultural enterprise concerns the enormous number of decisions it faces on a daily basis. In this way, decisions are made related to the activity of the research and development department, of the marketing, production, financial, human resources, etc. Strategic decisions are taken - of long-term scope and impact, or tactical decisions - narrower in terms of time horizon and complexity. In this complex gear of decisions, those regarding marketing particularly attract attention; through its own philosophy, marketing aiming not only at the simple attraction of customers, but - and only here begins the difficulty of its conception and practice -, ensuring their satisfaction after consumption. The solution of the difficult problems that the agricultural enterprise faces in the implementation of the marketing spirit in a scientific, modern way is carried out on the basis of a complex set of information, which allows it to correctly orient itself on the market and make the decisions that are optimal for it . Having valuable information, managers make marketing decisions burdened by the lowest dose of risk possible under the given conditions. Marketing research therefore provides precisely the information necessary for the organization to practice the modern marketing concept in its businesses.